IMPLEMENTATION OF TAHFIDZ AL-QUR’AN LEARNING METHOD AT MADRASAH ALIYAH GERPEMI TEBAS CLASS XI, SAMBAS REGENCY, WEST KALIMANTAN - Gusti Gusti; Hifza Hifza; Hamnah Hamnah (International Journal of Teaching and Learning, 2025)
This research aims to analyze the implementation of the Tahfidz Al-Qur’an learning method at Madrasah Aliyah Gerpemi Tebas, class XI, Tebas Sungai Village, Tebas District. The focus of this research includes the methods used, effectiveness in improving the quality of student memorization, and evaluation of the achievement of memorization targets. The approach used in this research is qualitative with a descriptive method. Data were obtained through observation, interviews with Tahfidz instructors, and documentation of the learning process. The results show that the Tahfidz learning method applied includes the Talaqqi and Murajaah methods, with regular memorization recitation sessions. Learning begins with students reciting their memorization to the instructor, followed by repetition together to strengthen memory. Evaluation is conducted through two types of assessments: summative (every semester) and formative (monthly), to ensure the fluency, accuracy, and precision of student memorization. Although the method is quite effective in improving student memorization, some challenges remain, such as inconsistency in Murajaah practice and lack of motivation among students to achieve memorization targets. Therefore, additional strategies are needed, such as intensive guidance, stricter scheduling of Murajaah practice, and support from the madrasah and families to improve the results of Tahfidz learning in class XI.